Interest in Students with Disabilities in Participating in Physical Education Learning - Harum Mita Maharani; Aam Ali Rahman; Dewi Susilawati (Universitas Negeri Semarang, 2026)
This study aims to describe the level of interest of students with special needs in participating in physical education learning at special needs school, identify the factors that affect these interests, and describe the form of student participation during the learning process. This study applies a qualitative approach through case research methods. The number of participants in this study was 10 students with disabilities between the ages of 11 and 16, selected by purposive means. The data collection method included observation, an image-based questionnaire with an easy scale, and semi-structured interviews with Physical education, sports and health teachers. Data were analyzed descriptively for observation and questionnaires, as well as thematic analysis for interviews. The results of the study show that the interest of disabled students in participating in physical education learning in general is included in the medium to high category. The observation results showed that 50% of students had high interest, 30% moderate, and 20% low. The results of the questionnaire showed that the indicators of interest and attention tended to be high, while student activities were diverse. The main factors that affect students' interests include adaptive learning strategies, the use of learning media, the emotional bond between teachers and students, and a pleasant learning atmosphere. The interest of students with special needs in physical education learning is relatively good and is influenced by various internal and external factors. Overall, the study concludes that the interest of students with special needs in physical education is relatively good and is shaped by a combination of internal and external factors, especially effective teaching approaches and supportive learning conditions.